Reactualization of Multicultural Instruction in Pondok Pesantren: Organism Models of PAI Development Based on Inter, Multi and Transdisciplinary - Munir, Samsul (Didaktika Religia, 2018)
Contemporarily, globalization marked by every access in all fields has created a variety of problems in people's lives. In reality, the world now (as a product of globalization) is almost entirely dominated by Europe and the United States which clearly have different cultural roots with the Indonesian culture. The hegemony that occurs is not merely economical and political, but more than that, it is also the cultural project of modernity. The impact of globalization today has been able to uproot the Indonesian people from the cultural roots that become their inheritance. Dehumanization in the form of an acute moral crisis has also become a part that is almost inherent in the life of every human being. In this context, pesantren as Islamic institutions that are rich of the characteristics of the Indonesian people have strategic values in the development of a multicultural society. For the Indonesian people, the strategic role of pesantren in globalization as a moral development institution, da'wah institution, and educational institutions with a multicultural character and nationalism will greatly determine the direction and purpose of the future of the Indonesian people. The response of pesantren in addressing globalization in accordance with the roles and fields that they have worked on, "namely the field of moral guidance that is oriented live together through applied learning" will become urgent as a way of life among Islamic community of Indonesia. In this regard, the study on the role of pesantren in actualizing the multicultural insightful learning process will focus on: first, the actualization of the PAI system in Islamic boarding schools in the era of globalization; second, models of PAI development at Islamic boarding schools; third, the development of the PAI system with the model of organisms in Islamic boarding schools.